Serum type III procollagen and basement membrane proteins as noninvasive markers of hepatic pathology in Indian childhood cirrhosis - Trivedi, P; Risteli, J; Risteli, L; Tanner, M S; Bhave, S; Pandit, A N; Mowat, A P (Hepatology (Baltimore, Md.), 1987)
While serum concentrations of antigens of the aminopropeptide of type III procollagen have been considered as indicators of hepatic pathology in adults, the high concentrations normally found in children during growth may preclude their use in pediatric liver disease. To clarify this and to determine the role of other circulating connective tissue-related substances in children, we have measured serum concentrations of antigens related to aminopropeptide of type III procollagen, the 7S domain of type IV collagen and the P1 fragment of laminin in healthy subjects aged 1 month to 4 years and in children with Indian childhood cirrhosis, a particularly aggressive form of liver disease. In healthy subjects, there was a considerable age variation in serum aminopropeptide of type III procollagen but not in 7S collagen or laminin P1. In Indian childhood cirrhosis, all three serum antigens were increased (p less than 0.001) above the upper limit of normal for age. Both the serum 7S collagen and laminin P1 concentrations showed a significant correlation with the degree of intralobular fibrosis and also with the severity of necrosis and cellular infiltration, suggesting that these serum antigens may be a noninvasive means of assessing and monitoring events associated with hepatic fibrosis in Indian childhood cirrhosis. The raised serum aminopropeptide of type III procollagen in Indian childhood cirrhosis did not correlate with any histological parameter assessed. Gel filtration of serum showed that, in healthy subjects, the predominant antigenic form of aminopropeptide of type III procollagen was a degradation peptide smaller than authentic aminopropeptide of type III procollagen; while in Indian childhood cirrhosis the authentic peptide and a larger degradation peptide predominated.